HBV and HCV in Health care workers and students of a newly established Tertiary care hospital at Rishikesh: Prevalence and immunity status - Gupta, Pratima; Kaistha, Neelam; Omar, Balramji (Indian Journal of Community Health, 2020)
Background: Hepatitis B and C cause serious infectious disease of the liver which affects millions of people worldwide. More than 2 billion people living today have been infected with Hepatitis B virus (HBV) at some time in their lives and about 350 million people are carriers of the virus. Aim: To detect HBV and HCV infection and assess HBV immunity status amongst healthcare workers, medical students and nursing students at AIIMS Rishikesh. Methods: 135 participants (Medical faculty, Nursing Faculty, Resident Doctors, laboratory technicians, laboratory attendants, medical and nursing students) were enrolled for the study. Serological tests HBsAg, anti-hepatitis C virus antibodies (anti-HCV), anti-HBs antibodies, were performed. None were positive for HBsAg 1.5% were positive for Anti HCV antibodies and 61.75% had protective levels of antiHBs. Conclusion: HBV vaccination and screening for HBV, HCV, and anti-HBs of all HCW and students at time of entry should be done. Yearly screening thereafter should be done to check as follow up. Regular training on HBV vaccination and safe practices should be emphasized at all levels of HCW.